Faktor-Faktor Yang Mempengaruhi Corporate Social Responsibility Pada Perusahaan Property dan Real Estate Yang Terdaftar Di Bursa Efek Iindonesia Tahun 2018-2022 - febrianti, pepti; Mikial, Msy; Armereo, Crystha (Jurnal Nusa Akuntansi, 2024)
This research aims to determine the factors that influence corporate social responsibility in property and real estate companies listed on the Indonesian Stock Exchange in 2018-2022. This research uses a quantitative type of research with a sampling technique using a purposive sampling method and a data collection technique using documentation data taken from the Indonesian Stock Exchange. Data were analyzed using descriptive statistical tests, normality tests, classical assumption tests, multiple linear regression tests, hypothesis tests and coefficient of determination tests with the help of SPSS. The results of this research show that simultaneously tax aggressiveness and liquidity have an effect on corporate social responsibility in property and real estate companies listed on the Indonesian Stock Exchange in 2018-2022, then partially tax aggressiveness has no effect on Corporate Social Responsibility in property and real estate companies listed on the Indonesian Stock Exchange in 2018-2022, while liquidity influences Corporate Social Responsibility in property and real estate companies listed on the Indonesian Stock Exchange in 2018-2022.